Analysis of transmission speed of AX.25 Protocol implemented in satellital earth station UPTC - Oscar Fernando Vera Cely; Jairo Alonso Mesa Lara; Roberto Ferro Escobar (Tecnura, 2015)
One of the important parameters for the proper functioning of satellital ground station projected on Pedagogical and Technological University of Colombia (UPTC) is the efficiency in transmission speed on communications protocol. This paper shows the results of analysis of the transmission speed of the AX.25 protocol implemented in the communication system of the satellital ground station UPTC. It begins with a brief description of the implemented hardware; the behavior of the transmission rate is evaluated using a theoretical analysis based on equations to estimate this parameter in the operation of the protocol, then tests are performed using the hardware that the satellital ground station UPTC has and finally, the conclusions are presented. Based on comparison of the theoretical analysis results obtained experimentally, it became apparent that AX.25 protocol efficiency is higher when increasing the number of frames.